1995
DOI: 10.1073/pnas.92.13.6157
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mammalian retinoid X receptors by the insect growth regulator methoprene.

Abstract: We report that methoprene and its derivatives can stimulate gene transcription in vertebrates by acting through the retinoic acid-responsive transcription factors, the retinoid X receptors (RXRs). Methoprene is an insect growth regulator in domestic and agricultural use as a pesticide. At least one metabolite of methoprene, methoprene acid, directly binds to RXR and is a transcriptional activator in both insect and mammalian cells. Unlike the endogenous RXR ligand, 9-cis-retinoic acid, this activity is RXR-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
1
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(132 citation statements)
references
References 22 publications
(30 reference statements)
2
127
1
2
Order By: Relevance
“…Although there is evidence that the primary target of JH action is at the plasma membrane in the particular cases of the male accessory gland of D. melanogaster and the ovarian follicular epithelium of Rhodnius prolixus [56ĎŞ58], because of its molecular nature as a small, hydrophobic compound, it has been hypothesized that JH influences gene expression similarly as steroid, thyroid and retinoid hormones do. Indeed, Harmon et al [59] have demonstrated that methoprene acid, a derivative of the JHA methoprene, can bind directly to mammalian retinoid X receptors and confers gene activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence that the primary target of JH action is at the plasma membrane in the particular cases of the male accessory gland of D. melanogaster and the ovarian follicular epithelium of Rhodnius prolixus [56ĎŞ58], because of its molecular nature as a small, hydrophobic compound, it has been hypothesized that JH influences gene expression similarly as steroid, thyroid and retinoid hormones do. Indeed, Harmon et al [59] have demonstrated that methoprene acid, a derivative of the JHA methoprene, can bind directly to mammalian retinoid X receptors and confers gene activation.…”
Section: Discussionmentioning
confidence: 99%
“…Degitz et al (2000) reported that 6.25 Îźg/l all trans retinoic acid could elicit higher teratological rate and mortality of exposed Xenopus laevis. Methoprene acid, a metabolic degradation product of methoprene, a pesticide, and organochlorine pesticides have been shown to bind to members of the retinoic acid receptors (RAR) (Harmon et al, 1995;Lemaire et al, 2005). Although up to now, it is not clear whether the reported increase of teratological rates of Japanese medaka embryos were related to retinoids in the secondary effluent, the above adverse ecological effects should be considered when the secondary effluent from the STPs is used as the main supplementation water source for surface water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Because 9-cis-RA is considered the principal ligand for RXRs, the absence of detectable 9-cis-RA raises the question as to which ligands drive the RXR activation observed by Solomin et al (1998) starting at 11 dpc. One possibility is that 9-cis-RA appears at later stages than assayed by Horton and Maden (1995), another is that 9-cis-RA is present but below the limit of detection, and a third is that RXR activation is driven by other ligands (Eager et al, 1992;Harmon et al, 1995;Kitareewan et al, 1996) or by ligand-independent mechanisms such as phosphorylation (Lefebvre et al, 1995;Rochette-Egly et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Because retinoid receptors can also be activated by compounds other than retinoids (Eager et al, 1992;Harmon et al, 1995;Kitareewan et al, 1996), and we obtained a prominent peak that is not a retinoid, we assayed other potential ligands, focusing on relevant fatty acids. Arachidonic acid (ARA), docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA) standards were all detectable with our ECD system, but none of these corresponded to any of the peaks in the tissue chromatograms.…”
Section: Axial Profiles Of Endogenous Retinoidsmentioning
confidence: 99%